The relationship between cognitive inhibition and extraversion/introversion - Knapp, Alexandra Elizabeth, author; Campbell, Alana May, author; Burr, Hilary Kay, author; Matigian, Morgan Ashley, author; Davalos, Deana, author (Colorado State University. Libraries, 2009)
The purpose of this study was to analyze the visual and textual content presented on the covers of Seventeen magazines published between 1997 and 2007. Seventeen is the most widely read magazine among adolescent females today (SRDS, 2002); research suggests that young readers look to this publication for ideas about who to be and how to look (Duffy and Gotcher, 1996). Covers were chosen for analysis because they represent an index to the information included within the magazine and serve as an advertisement for the sale of the publication. Since young people look to Seventeen magazine for insight on how to look and act, it is important to be aware of what they are being told and shown.
Keywords: behavioral approach system; behavioral inhibition system; BAS; BIS; cognitive inhibition; introverts; extraverts